Feminist Stylistics Analysis of the Movie “Gangubai Kathiawadi”: The Queen of Kamathipura who Defied Gender Inequality - Afandi, Fahri; Salim, Fahri; Nabila, Kanaya Nur; Meisya, Shalsa Billa; Rangkuti, Rahmadsyah (Universitas Pahlawan Tuanku Tambusai, 2025)
This research was aimed at analyzing gender inequality and social discrimination in the movie “Gangubai Kathiawadi” describing how women and gender roles presented in texts by applying a feminist approach. Through a qualitative descriptive approach, this study explores the dialogue in the movie at three different levels; words level, phrase/sentence level, and discourse level. The primary objective of this research is to see how gender bias is depicted through texts. One of the main findings of this study is that women in brothels are often treated as lawbreakers, even though they are often in oppressive situations and how the main character in this movie tries to fight for the rights and integrity of women. The dialogue in the movie successfully depicts the injustice experienced by women. Reinforcing the idea that justice, security, and a decent life are the rights of all women, regardless of their jobs.